2010
DOI: 10.1080/09511920903527846
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach to modelling human systems as reuseable components of manufacturing workplaces

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…Studies on human issues still showed ambiguity in terms of how CM deals with human aspects in a cellular manufacturing environment (Eckstein and Rohleder, 1998). The human system is a term used to surmise the systematic study of competent people working as an individual or as a group performing a structured set of activities (Ajaefobi et al, 2010). The difficulty to model human is due to the complex behaviour of human depending on the roles, the situation and their knowledge level (Ajaefobi et al, 2006).…”
Section: Human Systems Model In CMmentioning
confidence: 99%
“…Studies on human issues still showed ambiguity in terms of how CM deals with human aspects in a cellular manufacturing environment (Eckstein and Rohleder, 1998). The human system is a term used to surmise the systematic study of competent people working as an individual or as a group performing a structured set of activities (Ajaefobi et al, 2010). The difficulty to model human is due to the complex behaviour of human depending on the roles, the situation and their knowledge level (Ajaefobi et al, 2006).…”
Section: Human Systems Model In CMmentioning
confidence: 99%
“…A number of factory design methods (Iqbar and Hashmi, 2001, Sheth, 1995, Wiendahl et al, 2002 and techniques (Womack and Jones, 2003, Bicheno, 2000, Kosanke, 1996, Hines et al, 2004 have literature on this can be found in Weston, 2007, Chatha and Resource selection ontologies for factory design Ajaefobi, 2004, Ajaefobi et al, 2010, Khalil and Weston, 2010.…”
Section: Some Advances In Digital Factory Design Methodsmentioning
confidence: 99%
“…Manufacturing Enterprises (MEs) are faced with intense competition arising from internal and external changes, which induce dynamics directly or causally on products, processes and their associated resources (Agyapong-Kodua and Weston, 2011, Ajaefobi et al, 2010, Weston et al, 2006. Many causally and/or temporarily related factors may induce these changes and lead to complex and difficult to predict dynamics (Agyapong-Kodua, 2009, Sterman, 2000, Richardson, 1999, Wolstenholme, 1999, Scholz-Reiter et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many good research works on workflow resource management mainly concerns the functions of workflow management systems (Russell et al 2005) or improving the process design (Ly et al 2006, Rinderle-Ma andvan der Aalst 2007). Although human resource is very important for workflow management (Moore 2002, Ajaefobi et al 2010, their behaviour patterns in workflow runtime stage still need to be discovered.…”
Section: Introductionmentioning
confidence: 99%